Nautilus: A Bioinformatics Package for the Analysis of HIV Type 1 Targeted Deep Sequencing Data - Kijak, Gustavo H. (Mary Ann Liebert, Inc., 2013)
The advent of next generation sequencing technologies is providing new insight into HIV-1 diversity and evolution, which has created the need for bioinformatics tools that could be applied to the characterization of viral quasispecies. Here we present Nautilus, a bioinformatics package for the analysis of HIV-1 targeted deep sequencing data. The DeepHaplo module determines the nucleotide base frequency and read depth at each position and computes the haplotype frequencies based on the linkage among polymorphisms in the same next generation sequence read. The Motifs module computes the frequency of the variants in the setting of their sequence context and mapping orientation, which allows for the validation of polymorphisms and haplotypes when strand bias is suspected. Both modules are accessed through a user-friendly GUI, which runs on Mac OS X (version 10.7.4 or later), and are based on Python, JAVA, and R scripts. Nautilus is available from www.hivresearch.org/research.php?ServiceID=5&SubServiceID=6.